Fenton degradation of linear alkylbenzene sulphonates (LAS) - Abu Hassan, Mohd Ariffin; Yusof, Rozilawati; Muhamad, Siti Hajar Anaziah (Faculty of Chemical and Natural Resources Engineering, UTM, 2007)
Among Advanced Oxidation Processes (AOPs), Fenton's reagent has been efficiently used as a chemical process for wastewater treatment. Fenton's reagent is used to treat a variety of industrial wastes containing a range of toxic organic compounds. Fenton system consists of ferrous salts combined with hydrogen peroxide under acidic condition. The effect of Fenton degradation of linear alkylbenzene sulphonates (LAS) at different initial concentration (0.1x10(-3) mol/L, 0.25 x10(-3) mol/L and 0.5x10(-3) mol/L) was investigated. All experiments used a temperature of 30°C, stirring speed of 125 rpm, a reaction time of 90 min and initial pH of 3.0. It was found that 82%, 64% and 49% of TOC removals were achieved at 0.1x10(-3) mol/L, 0.25x10(-3) mol/L and 0.5x 10(-3) mol/L respectively. It was also found that the main degradation of LAS proceeds via reaction with OH• radicals. The addition of sodium benzoate, an OH• radical scavenger was inhibited and retarded the oxidation. For instance, 28 % and 82 % of TOC removals were achieved in the presence and absence of radical scavenger at LAS concentration of 0.25x 10(-3) mol/L.